2015
DOI: 10.1007/s00280-015-2881-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose capecitabine plus trastuzumab as first-line treatment in patients 75 years of age or older with HER2-positive advanced gastric cancer: a pilot study

Abstract: Low-dose capecitabine plus trastuzumab is effective and well tolerated in elderly patients with HER2-positive AGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…Given that not increasing toxicity in a more vulnerable group is generally deemed favorable, it would be advisable to continue to explore adapted schedules that minimize toxicity. On the other hand, despite the paucity of literature on this subject, our data also support the conclusions of other, small series that suggest that trastuzumab is safe and effective in older patients (26,27).…”
Section: Discussionsupporting
confidence: 88%
“…Given that not increasing toxicity in a more vulnerable group is generally deemed favorable, it would be advisable to continue to explore adapted schedules that minimize toxicity. On the other hand, despite the paucity of literature on this subject, our data also support the conclusions of other, small series that suggest that trastuzumab is safe and effective in older patients (26,27).…”
Section: Discussionsupporting
confidence: 88%
“…A phase 3, open-label randomized controlled trial showed that trastuzumab in combination with chemotherapy exhibits both efficacy and safety for the first-line treatment of advanced gastric cancer with expression of HER2 [6]. In addition, in several clinical trials, trastuzumab in combination with chemotherapy reveals promising antitumor activity with manageable toxic effects [710]. Although the outcomes are encouraging, HER2 positive rate in gastric cancer patients is quite low, which means that only a small subgroup of patients can benefit from anti-HER2 target therapy.…”
Section: Introductionmentioning
confidence: 99%
“…22,32 The addition of triplet cytotoxic backbones to trastuzumab consisting of docetaxel, platinum and fluoropyrimidine did not increase survival over ToGA, as did regimens in which trastuzumab was combined with another targeted agent bevacizumab plus a cytotoxic triplet backbone. However, the fact that older and frailer patients were included in two of these singlet backbone studies is a plausible explanation for these findings, and the results should therefore be interpreted with caution.…”
Section: Discussionmentioning
confidence: 97%
“…However, the fact that older and frailer patients were included in two of these singlet backbone studies is a plausible explanation for these findings, and the results should therefore be interpreted with caution. 22,32 The addition of triplet cytotoxic backbones to trastuzumab consisting of docetaxel, platinum and fluoropyrimidine did not increase survival over ToGA, as did regimens in which trastuzumab was combined with another targeted agent bevacizumab plus a cytotoxic triplet backbone. This implicates that there is currently no role for triplet cytotoxic backbones and for bevacizumab in the first-line trastuzumab-based regimen.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation